Regional Russian Books of Memory as a Form of Preservation and Transfer of Cultural-Historical Memory about the Afghanistan War of 1979-1989 - Taisiya V. Rabush (RUDN Journal of Russian History, 2021)
The historical memory of the Soviet military intervention in Afghanistan (1979-1989) is studied through the prism of memory books dedicated to the participants of the war and those who died in it. The present paper is the first study of the Afghan books of memory that were published over the past decades in different regions of Russia. The first part of this paper analyzes the regional books of memory published in various regions of the Russian Federation from 1991 to the present day; the second part analyzes the books of memory published in small cities of Russia as a separate cultural phenomenon. In conclusion, the author describes the main features of regional Afghan books of memory, emphasizing that the memory books are published with the active participation of various regional organizations - from local archives to representatives of municipalities - revealing that the publication of these books is part of cultural policy in the regions. Many memory books have been reprinted, which indicates the continued collection and processing of information about the military casualties in Afghanistan. The regional books of memory are one of the most important forms of preserving and transmitting the historical memory of the Afghanistan war.